2019
DOI: 10.1186/s12985-019-1227-4
|View full text |Cite
|
Sign up to set email alerts
|

Mouse-adapted H9N2 avian influenza virus causes systemic infection in mice

Abstract: BackgroundH9N2 influenza viruses continuously circulate in multiple avian species and are repeatedly transmitted to humans, posing a significant threat to public health. To investigate the adaptation ability of H9N2 avian influenza viruses (AIVs) to mammals and the mutations related to the host switch events, we serially passaged in mice two H9N2 viruses of different HA lineages — A/Quail/Hong Kong/G1/97 (G1) of the G1-like lineage and A/chicken/Shandong/ZB/2007 (ZB) of the BJ/94-like lineage —and generated tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…The virus had been completely eliminated from the lungs of H9N2-infected mice by 14 dpi, and lung histopathology in H9N2-infected mice was similar to that in mock-infected mice at 14 dpi. These results showed that H9N2 virus infection caused obvious respiratory diseases in BALB/c mice and mice infected with H9N2 virus had recovered by 14 dpi, which was consistent with our previous and other published research findings ( 38 40 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The virus had been completely eliminated from the lungs of H9N2-infected mice by 14 dpi, and lung histopathology in H9N2-infected mice was similar to that in mock-infected mice at 14 dpi. These results showed that H9N2 virus infection caused obvious respiratory diseases in BALB/c mice and mice infected with H9N2 virus had recovered by 14 dpi, which was consistent with our previous and other published research findings ( 38 40 ).…”
Section: Discussionsupporting
confidence: 93%
“…The virus had been completely eliminated from the lungs of H9N2-infected mice by 14 D.P.I., and lung histopathology in H9N2-infected mice was similar to that in mock-infected mice on 14 D.P.I. These results showed that H9N2 virus infection caused obvious respiratory diseases in BALB/c mice and mice infected with H9N2 virus had recovered by 14 D.P.I., which were consistent with our previous and other published research findings(38)(39)(40).Although influenza virus alone could cause a substantial impact on global health, secondary bacterial infections post-influenza are associated with increased morbidity and mortality during both epidemic and pandemic influenza(23). Secondary bacterial on March 21, 2021 by guest http://iai.asm.org/ Downloaded from pneumonia, particularly from S. pneumoniae, accounts for more than 95% and 50% of severe illnesses and deaths that occurred during 1918 pandemic and 2009 pandemic, respectively(17-20).…”
supporting
confidence: 91%
“…In general, H9N2 infections in poultry or human are mild. However, some H9N2 AIVs were reported to cause lethal infection in mice (20)(21)(22). To better understand the mechanisms, we generated a mouse-lethal recombinant H9N2 AIV (V K627 -NanoLuc virus) to analyze the real-time infection dynamic of H9N2 AIV in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the H9N2 AIVs generally caused mild infections in poultry, even in humans. Notably, some H9N2 AIVs were found to replicate efficiently and possess lethality in mice (20)(21)(22), but the viral infection dynamics in vivo and the detailed mechanisms of increased pathogenicity of H9N2 AIVs to mice remain unclear, posing a potential threat to public health.…”
Section: Introductionmentioning
confidence: 99%
“…This process involves infecting mice with the wild type strain, collecting mouse lungs at one to three days post infection, homogenizing lung tissues and then infecting another mouse with diluted lung homogenates. Some viruses are easily adapted to mice, however other viruses may take several passages before they are fully adapted [ 122 , 123 , 124 , 125 ]. Mouse adaptation can cause mutations in many viral genes, including the polymerase machinery (PB1, PB2 and PA) as well as the glycoproteins HA and NA [ 126 , 127 , 128 ].…”
Section: Animal Models Used In Influenza Virus Vaccine Studiesmentioning
confidence: 99%